Sex Offenders of East Asian Heritage Resemble Other Canadian Sex Offenders - Lee, Seung C. (Asian journal of criminology, 2018)
Although there is considerable research on Caucasian sexual offenders, there has been much less research on sex offenders of Asian heritage. The current study compared East Asian (e.g., Chinese, Japanese, and Korean) sex offenders in British Columbia (B.C.), Canada, and other B.C. sex offenders on items and total score of Static-99R. This study included all provincially sentenced adult male sexual offenders (n = 4580) supervised in the community by B. C. Corrections (including 122 East Asian sex offenders). Sexual, violent, any crime, and any recidivism (including technical violations) data were collected with an average follow-up 4.3 years. The total scores of Static-99R were similar between East Asian sex offenders and other ethnic groups (M = 2.0 vs. M = 2.4). East Asian offenders scored significantly lower than other ethnic offenders on several items measuring general criminality (e.g., prior non-sexual violence, prior sentencing dates, and any prior sex offenses). In contrast, Asian offenders appeared to be more paraphilic (e.g., any convictions for non-contact sex offenses). Lastly, Static-99R significantly predicts sexual, violent, and criminal among sex offenders of East Asian heritage.